Media Analysis of News Articles During COVID-19: Renewal, Continuity and Cultural Dimensions of Creative Action - Mattson, David; Mathew, Katie; Katz-Buonincontro, Jen (Frontiers in Psychology, 2021)
Worldwide, the COVID-19 pandemic has forced people to adapt quickly, and to reexamine interactions and responsibilities towards communities in creative ways. This paper presents a qualitative media analysis (Altheide & Schneider, 2013) of fifty online news articles (Los Angeles Times and New York Times) published between March 17th and August 6th, 2020 using the key-words “creativity” and “COVID-19”. Informed by a definition of creativity as actions that are considered both “new” and “appropriate” (Sternberg & Lubart, 1999), articles describing a “creative action” were kept for analysis. These articles highlight creative responses to the COVID-19 quarantine in various domains including architecture, fashion, and faith. In this paper, we discuss the themes derived during this analysis- “renewal and continuity” and “the multidimensionality of creativity” which elaborate and contextualize a perspective of socio-cultural creativity theory and propose two implications of this study. The first implication posits that creativity was an observable, cultural response to the COVID-19 pandemic. The second implication offers a broader concept of how cultural resources function as dynamic constraints or “affordances” within the Five A’s model of creativity (Glaveanu, 2013). Discussion of further research through the lens of sociocultural creativity is discussed.